Circulating tumor DNA detection in MRD assessment and diagnosis and treatment of non-small cell lung cancer - Fang, Xiaoxu; Yu, Shaokun; Jiang, Yingying; Xiang, Yan; Lu, Kaihua (Frontiers in Oncology, 2022)
Circulating tumor DNA (ctDNA) has contributed immensely to the management of hematologic malignancy and is now considered a valuable detection tool for solid tumors. ctDNA can reflect the real-time tumor burden and be utilized for analyzing specific cancer mutations via liquid biopsy which is a non-invasive procedure that can be used with a relatively high frequency. Thus, many clinicians use ctDNA to assess minimal residual disease (MRD) and it serves as a prognostic and predictive biomarker for cancer therapy, especially for non-small cell lung cancer (NSCLC). Advanced methods have been developed to detect ctDNA, and recent clinical trials have shown the rationality and feasibility of ctDNA for identifying mutations and guiding treatments in NSCLC. Here, we have reviewed recently developed ctDNA detection methods and the importance of sequence analyses of ctDNA in NSCLC.